Gender differences in risk factors of benign vocal fold disease in Korea: the fifth Korea National Health and Nutritional Examination Survey. (2nd April 2016) - Byeon, Haewon
Abstract : The aim of this study was to confirm the prevalence rate of benign vocal fold disease (BVFD) based on gender in the Korean adult population and investigate potential risk factors of BVFD. Subjects were 8, 677 non-institutionalized civilian adults over the age of 19 (3, 788 males and 4, 899 females) who completed the laryngeal examination of the fifth Korea National Health and Nutrition Examination Survey. Poisson regression analyses were conducted to examine the potential risk factors of BVFD. The prevalence rates of BVFD were similar in men (2.7%) and women (2.6%). When adjusted for covariates, men with self-reported voice problems had a 6.7 times greater risk (RR 6.72, 95% CI 4.17–10.84) of BVFD ( P < 0.01). In addition, women with self-reported voice problems (RR 4.71, 95% CI 3.01–7.37) and current smokers (RR 1.97, 95% CI 1.01–3.81) were more likely to have BVFD ( P < 0.01). There are gender differences in the risk factors of BVFD. In order to prevent BVFD, the enactment of guidelines reflecting gender differences is required.